Review of Marine Fishes of the Arctic Region (Mecklenburg et al. 2018) - Hilton, Eric J. (Zootaxa, 2019)
In looking through the shelves of my library, it strikes me that there are two styles of faunal guide books within ichthyology: those that attempt to be authoritative and comprehensive (both taxonomically and biologically) and those that are more utilitarian, with a rare few that are able to pull off both formats. Both approaches have their strengths, and the results of both approaches display a wide degree of variation. The commonalities of successful examples for each approach include accessibility of information for the expert on a particular group of fishes, as well as the informed novice, the presentation of key points in clear and unambiguous fashion, and its usefulness as a contribution to future studies on the fauna, as no work will be the final word.